KEJADIAN DERMATITIS KONTAK AKIBAT KERJA DARI PROSES PRODUKSI PLYWOOD - Mariaman Tjendera; Andi Asda Astiah; mutiara, mutiara husnul khatimah (Universitas Batam, 2025)
ABSTRACT Background: Occupational contact dermatitis is one of the most common skin diseases among workers, which can lead to reduced productivity and increased absenteeism. Factors that trigger contact dermatitis can be grouped into two categories, namely direct causal factors, which include the nature of the substance, level of solubility, form (solid, gas or liquid), concentration, and duration of contact and indirect causal factors which include gender. , age, level of personal hygiene, ethnicity, use of personal protective equipment (PPE), and temperature and humidity conditions. Methods: The design of this research was a cross-sectional analytical observational study. Data was taken using a questionnaire and diagnosis from local health center doctors, sampling using total sampling technique and obtained 76 respondents from the plywood processing work division. Data analysis used univariate analysis and bivariate chi-square tests. Results: The results of the chi-square statistical test analysis showed that the relationship between the use of PPE and work-related contact dermatitis was found to be a p-value of 0.000, and the relationship between personal hygiene and work-related contact dermatitis was found to be a p-value of 0.000. Conclusion: There was a relationship between the use of PPE and personal hygiene on work-related contact dermatitis in plywood production process workers at PT. Lestarindo Utama Karya in 2024 Keywords: DKAK, PPE, Personal Hygiene, Plywood